Beyond GDP Is there a law of one shadow price? - Murtin, Fabrice (OECD Statistics Working Papers, 2015)
This paper builds a welfare measure encompassing household disposable income, unemployment and longevity, while using two different sets of "shadow prices" for non-income variables. The valuations of vital and unemployment risks estimated from life satisfaction data ("subjective shadow prices") and those derived from model-based approaches and calibrated utility functions ("model-based shadow prices") are shown to be broadly consistent once a number of conditions are fulfilled. Subjective shadow prices appear to be inflated by the downward bias on the income variable in life satisfaction regressions conducted at the individual level, while the latter bias is largely removed when running regressions at the country level. On the other hand, model-based shadow prices are typically underestimated as: i) the valuation of the unemployment risk is assumed to take place under the veil of ignorance (i.e. for a representative agent that has no information on her current or future unemployment situation); ii) the standard model relies on a Constant Relative Risk Aversion (CRRA) utility function, which has no specific relative risk aversion parameter for unemployment and vital risks; iii) the Value of Statistical Life that is used in standard calibration pertains to the adult lifespan while life expectancy at birth covers the entire lifetime